Performance of low frequency magnetic field meters to sinusoidal and beat-phenomenon magnetic fields - Cortes, Camilo A. (2006)
This paper presents the first part of a research work dealing with the performance assessment of commercially available magnetometers. The aim of the article is to make a comparative study on the accuracy of several magnetometers used today by agencies and research institutes to measure magnetic fields produced by power systems in public and work environments. There is still a lack in the knowledge about the measurement accuracy for the complex case of having several harmonic components like those usually present in distribution networks. The frequency behavior of several commercially available magnetometers has been analyzed using a calibrated Helmholtz coil. The accuracy of 41 magnetometers has been investigated during the research by measuring sinusoidal fields in the frequency range from 10 Hz to 10 kHz, including harmonic frequencies of 50 and 60 Hz, interharmonic frequencies and signals having small deviations from the fundamental frequency, and waveforms having beat phenomena. The results of the study show a lack of accuracy of some magnetometers at frequencies above 3 kHz, large errors at the 16.66 Hz frequency used in transportation systems, and increased errors were found in the rms measurement of beat-phenomenon waveforms. The increased error in this non-sinusoidal waveform type demands a deeper research on the accuracy of magnetometers when measuring non-sinusoidal waveforms.